The role of osteocalcin in regulating the acute stress response - Kang, Ning; Huang, Jie; Han, Xiaoguang; Li, Zhengqian; Yuan, Yi; Guo, Xiangyang; Yang, Ning (Frontiers in Pharmacology, 2025)
Osteocalcin (OCN), a bone-derived hormone, considered as an indicator of bone turnover. Beyond its canonical role in bone metabolism, OCN may have many other functions as well. Studies have shown that it may also regulate glucose and lipid metabolism, cognitive function, sexual function, and more. Recently, OCN has become one interesting hormone with potential effects on acute stress response (ASR), which is essential for vertebrates’ survival. This review aims to comprehensively summarize the progress on the role of OCN in the pathophysiology of ASR and to thoroughly analyze the molecular mechanisms and significance of OCN in modulating ASR. In summary, a deeper understanding of OCN’s role in the ASR will help reveal how bone-derived signals integrate into stress regulatory networks and may guide the development of novel strategies to prevent or treat stress-related disorders (e.g., anxiety, depression, or stress-aggravated cardiac events). By focusing on the emerging OCN–stress axis, our review highlights an expanding perspective on bone as an endocrine organ influencing stress physiology.